Pengaruh indeks harga saham gabungan dan suku bunga terhadap cryptocurrency - Rizaldy Insan Baihaqqy, Mochammad; Hidayat, Udin; Prasetyo, Yoyok (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
Cryptocurrency has become very popular among Indonesian people with a very significant increase in 2020. This is an interesting phenomenon to study, because Cryptocurrency in the form of bitcoin still does not have clear legality in 2020. Various previous studies have shown a relationship between the composite stock price index (IHSG) and interest rates with Cryptocurrency. This study uses a quantitative approach with an empirical method using 2020 research data. The results of the study show that the influence of IHSG and interest rates on cryptocurrency is different. IHSG has a positive effect, meaning that the higher the IHSG, the higher the Cryptocurrency. Meanwhile, the lower the interest rate, the higher the Cryptocurrency. This indicates consistency that IHSG and interest rates have an effect on Cryptocurrency in Indonesia.